Evaluation of Metabolizable Protein and Metabolizable Energy Values of Wolffia Meal [Wolffia globosa (L). Wimm.] in Broilers - Pooponpan, P.; Chinrasri, O.; Saenthaweesuk, S.; Chantiratikul , A. (International Journal of Poultry Science, 2011)
This study was conducted to investigate the metabolizable protein and metabolizable energy values of Wolffia meal in broilers. Twenty-four three-week-old broilers were divided into 2 groups of 12 birds each and kept individually in metabolic cages where the excreta could be collected. Birds in each group were randomly fed basal diet or basal diet mixed Wolffia meal at the ratio of 80:20. Their excreta were collected daily for 7 days. Diets and excreta of birds were analyzed for crude protein and gross energy. The metabolizable protein and metabolizable energy of Wolffia meal were estimated by using different methods. The results showed that metabolizable protein and metabolizable energy values of Wolffia meal in broilers were 34.46% of protein intake and 1,047.8 kcal/kg, respectively.